An efficient extraction and clean-up procedure for pesticide determination in olive oil - Sobhanzadeh, E.; Bakar, N.K.A.; Abas, M.R.; Nemati, K. (2011)
This work reports a simple, rapid, and effective extraction method based on liquid-liquid extraction (LLE) followed by matrix solid-phase dispersion-sonication for detection, identification and quantification of multiclass pesticides in virgin olive oil using liquid chromatography mass spectrometry (LC-QTOF-MS). LLE to extract pesticide residues in virgin olive oil was performed in order to study the centrifugation efficiency to obtain high recovery yield and low co-extract fat residue in the final extract. Different suitable parameters of MSPD procedure were evaluated, such as nature of dispersing phase, clean-up adsorbent, and volume of eluting solvent (acetonitrile) in different extraction conditions, with or without sonication. The best results were obtained using 5g of virgin olive oil, 2g of PSA as dispersant sorbent, 2g of Florisil/GCB (70:30 w/w) as clean-up sorbent, and 15mL of acetonitrile as eluting solvent under conditions of 15min ultrasonic bath at RT. Method validation was performed in order to study sensitivity, linearity, precision, and accuracy. Average recoveries ranged between 73.7 and 104.2 with relative SDs 5.3-13.4 at three concentration levels (25, 50, and 100Î¼g/kg). Detection and quantification limits ranged from 1.5 to 5Î¼g/kg and 3 to 9Î¼g/kg, respectively.